Evaluation of production performance of carp in a lentic freshwater sewage-fed polyculture pond - Manna, N K; Banerjee, S; Bhoumik, M L (Indian Journal of Fisheries, 2011)
Results of composite fish culture operations in three tier systems conducted in asewage-fed fish farm in Bandipore, North 24-Parganas, West Bengal arepresented. Fish culture was carried out using four species combination of rohu,catla, mrigal and silver carp in first and third phases and five species combinationof rohu, catla, mrigal, silver carp and common carp in the second phase. The grossproduction offish was 924.56 kg/ha/90 days in phase-1,1116.68 kg/ha/BS days inphase-II and 1691.63 kg/ha/90 days in phase-Ill with stocking densitites of 20,000,25,000 and 15,000 per hectare respectively. Silver carp registered maximum dailygrowth performance (0.718 + 0.398 g to 2.109 + 0.081 g) followed by mrigal (0.653+ 0.098 g to 1.075 ± 0.101 g), rohu (0.466 ± 0.11 g to 0.984 ± 0.099 g), catla (0.341+ 0.102 g to 0.997+0.11 g) and common carp (0.385 ± 0.022 g). A critical analysisis made on production potentialities on the waste water impoundment in respectof stocking densities, species combinations and management procedures